Laminins Regulate Placentation and Pre-eclampsia: Focus on Trophoblasts and Endothelial Cells - Liu, Min; Yin, Yangxue; Yu, Hongbiao; Zhou, Rong (Frontiers in Cell and Developmental Biology, 2020)
Pre-eclampsia is a systemic vascular disease characterized by new-onset hypertension and/or proteinuria at ≥20 weeks of gestation and leads to high rates of maternal and perinatal morbidity and mortality. Despite the incomplete understanding of pre-eclampsia pathophysiology, it is accepted that insufficient spiral artery remodeling and endothelial dysfunction are major contributors. Laminins (LNs) are a vital family of extracellular matrix molecules present in basement membranes that provide unique spatial and molecular information to regulate implantation and placentation. LNs interact with cell surface receptors to trigger intracellular signals that affect cellular behavior. This mini-review summarizes the role of LNs in placental development during normal pregnancy. Moreover, it describes how LN deficiency can lead to the pre-eclampsia, which is associated with trophoblast and vascular endothelial dysfunction. New research directions and the prospect of clinical diagnosis of LN deficiency are discussed, and the gaps in basic and clinical research in this field are highlighted.